The synthesis and characterisation of the perylene acid dye inks for digital textile printing. (April 2019) - Choi, Sol; Cho, Kwan Hyun; Namgoong, Jin Woong; Kim, Jeong Yun; Yoo, Eui Sang; Lee, Woosung; Jung, Jae Woong; Choi, Jun
Abstract: Five perylene acid dyes were synthesized to manufacture water-based inks for the high-speed ink jet printing process, including digital textile printing. All the synthesized perylene dyes exhibited superior stability and optical properties compared to a commercially used azo dye. Their water solubility was efficiently enhanced by introducing bulky and hydrophilic substituents to ensure excellent long-term stability when formulated as water-based inks. The water-based inks with these perylene dyes showed outstanding print clarity with the colours different from the basic colour composition of the existing digital textile printing inks. They also exhibited good ejection performance and helped conduct well-controlled pattern printing when used in a commercial ink jet printing machine. Graphical abstract: Highlights: The five Perylene acid dyes were synthesized and suitably formulated into inks. The optical properties and the stability of synthesized dyes were excellent. The long-term stability of the prepared inks was excellent. The inks were helpful for expressing the expanded colour range in DTP application. The inks exhibited excellent ejection properties during inkjet printing.